HYPERHOMOCYSTEINEMIA AND ISCHEMIC STROKE - N. V. Pizova (Медицинский совет, 2017)
The article deals with the role of homocysteine in the human body. The amino acid homocysteine is a product of methionine demethylation. When the level of homocysteine increases, it damages the tissue structures of the arteries, initiating the release of cytokine, cyclins and other mediators of the inflammation. Its accumulation results in the loosening of arterial walls, formation of local defects in endothelium, which in turn leads to deposition on the cardiovascular wall of cholesterol and calcium. Hyperhomocysteinemia as a consequence of disturbed homocysteine metabolism is considered an independent factor in the risk of human stroke. The role of neuroprotective therapy in interrupting or decelerating the sequence of damaging biochemical and molecular processes capable of causing irreversible coronary damage to the brain is demonstrated.